HUBUNGAN WAKTU PEMBERIAN KONSELING KONTRASEPSI TERHADAP PEMILIHAN ALAT KONTRASEPSI PADA AKSEPTOR KB DI RUMAH BERSALIN MITRA ANANDA PALEMBANG TAHUN 2021 - Reni Saswita (Jurnal Kesehatan dan Pembangunan, 2022)
According to data from the WHO (2019), among 1.9 billion women of childbearing age (15-49 years) living in the world in 2019, 1.1 billion need family planning. Family Planning Counseling is a very important aspect of Family Planning and Reproductive Health services. The purpose of this study was to determine the relationship between the time of giving contraceptive counseling to the selection of contraceptives for family planning acceptors at the Mitra Ananda Maternity Hospital Palembang. The research used a cross sectional method. The population were all family planning acceptors who visited the Mitra Ananda with a total sample of 37 respondents. The results showed that the number of respondents whose selection of contraception was appropriate was 22 respondents (59.5%), most of the respondents received contraceptive counseling during ANC as many as 19 respondents (51.4%). The results showed that there was a significant relationship between the time of giving contraceptive counseling to the selection of contraceptives for family planning acceptors with P value = 0.032. Suggestions are expected to improve counseling and counseling to prospective family planning acceptors carried out during ANC so that prospective acceptors can have a longer time in considering the contraceptive to be used.